Industrial research on the quality of brake shoes meant for rolling stock. Issue 1 (January 2016) - Popa, E; Pascu, L; Socalici, A; Lascufoni, A
Abstract: Brake shoes wear appears as a normal exploitation process and depends both on the braking force and on the material the shoe is made of. Brake shoes are made of molded sulfurous cast iron. The industrial research and experiments aim at determining the specific characteristics of the phosphorous cast iron (chemical and structural homogeneity, hardness) and their optimization in view of improving the quality of the brake shoes meant for the rolling stock